Joint Associations of Dual Sensory Impairment and No-Activity Involvement With 1-Year Mortality in Nursing Homes: Results From the SHELTER Study - Yamada, Yukari; Denkinger, Michael D; Onder, Graziano; van der Roest, Henriëtte G; Finne-Soveri, Harriet; Bernabei, Roberto; Topinkova, Eva (The journals of gerontology. Series A, Biological sciences and medical sciences, 2016)
BACKGROUND: Concurrent vision and hearing impairment, known as dual sensory impairment (DSI), is associated with increased mortality. We aimed to examine individual and joint associations of DSI and involvement in activities with mortality in a large European nursing home study. METHODS: In total, 2,851 nursing home residents in 59 facilities in eight countries were followed for 1 year in the Services and Health for Elderly in Long TERm Care study. Vision and hearing impairment and average time of involvement in activities were assessed by trained research staff using the interRAI Long Term Care Facilities. Association between DSI and 1-year all-cause mortality was examined using Cox proportional hazards models adjusted for age, sex, facility, diagnoses of coronary heart disease and diabetes mellitus, self-rated health, end-stage disease, and functional and cognitive status. The modifying effect of involvement in activities on the association was investigated by the additive hazard model. RESULTS: DSI, defined as moderate to severe impairment in both senses, was independently associated with a 35% increased risk of 1-year mortality compared with non-DSI. Residents with DSI who were involved in activities did not have higher mortality, while residents with DSI who were not involved in activities had 51% higher mortality than non-DSI residents who were involved in activities, equivalent to approximately 209 additional deaths per 1,000 person-years (p = .012) due to the interaction between DSI and no involvement in activities. CONCLUSIONS: DSI is associated with increased mortality at nursing homes when combined with no involvement in activities.
Keywords: Human Activities; proporcionální rizikové modely; Nursing Homes; Humans; Vision Disorders; Case-Control Studies; Proportional Hazards Models; studie případů a kontrol; Nursing home issues; Female; rizikové faktory; Aged; lidské činnosti; věkové faktory; Time Factors; senioři; nedoslýchavost; lidé; Geriatric Assessment; Mortality; časové faktory; Dual sensory impairment; ženské pohlaví; Male; Aged, 80 and over; Additive hazards model; senioři nad 80 let; Age Factors; poruchy zraku; míra přežití; mužské pohlaví; geriatrické hodnocení; Hearing Loss; pečovatelské domovy; Risk Factors; Survival Rate